CRISPR typing and phage content of colonizing Group B Streptococci from healthy Egyptian women - Shabayek, Sarah; Haider, Dorina; Vogel, Verena; Khan, Uzma Basit; Jamrozy, Dorota; Jauneikaite, Elita; LeDoare, Kirsty; Bentley, Stephen; Spellerberg, Barbara (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundStreptococcus agalactiae or Group B Streptococcus (GBS) causes serious infections in neonates with a particularly high burden of disease in Africa. Maternal vaginal colonization is the primary source of neonatal transmission. Molecular surveillance of the maternal GBS population is crucial for informing maternal vaccine development and monitoring of the global circulation of GBS clones.MethodsThe current study analyzes the structure and diversity of the clustered regularly interspaced palindromic repeat (CRISPR)-associated (Cas) system and phage content in colonizing GBS isolates collected from healthy pregnant women from Ismailia, Egypt. The isolates were characterized by whole-genome sequencing within the global JUNO project.ResultsCRISPR arrays and phages were detected in a vast majority of GBS isolates. A strong congruence was observed between multilocus sequence typing (MLST), CRISPR profile, and phage content. Region-specific sequence types (STs) observed only in Africa were distinguishable from other lineages.ConclusionsCRISPR typing is a promising low-cost tool for investigating the population structure of GBS clones, particularly in middle- and low-income countries.